China's gilded age : the paradox of economic boom and vast corruption - Ang, Yuen Yuen, ....- (Cambridge : Cambridge University Press, 2020)
Why has China grown so fast for so long despite vast corruption? In China's Gilded Age, Yuen Yuen Ang maintains that all corruption is harmful, but not all types of corruption hurt growth. Ang unbundles corruption into four varieties: petty theft, grand theft, speed money, and access money. While the first three types impede growth, access money - elite exchanges of power and profit - cuts both ways: it stimulates investment and growth but produces serious risks for the economy and political system. Since market opening, corruption in China has evolved toward access money. Using a range of data sources, the author explains the evolution of Chinese corruption, how it differs from the West and other developing countries, and how Xi's anti-corruption campaign could affect growth and governance. In this formidable yet accessible book, Ang challenges one-dimensional measures of corruption. By unbundling the problem and adopting a comparative-historical lens, she reveals that the rise of capitalism was not accompanied by the eradication of corruption, but rather by its evolution from thuggery and theft to access money. In doing so, she changes the way we think about corruption and capitalism, not only in China but around the world.